Online entrepreneurship learning: A case study of a technical public university - Ahamat, Amiruddin (Inderscience Publishers, 2023)
An online learning platform is a network of interconnected interactive online services that provide lecturers, students and people interested in education with the knowledge, tools and resources necessary to support and improve the process and management of education. The purpose of this research is to examine the challenges that arise during an entrepreneurship course delivered via online learning platforms. The methodology used in this study employs qualitative methodologies to ascertain students’ intentions to become entrepreneurs. Interviews were conducted to elicit information about the materials used in the entrepreneurship course delivered via online learning platforms, as well as the obstacles and limits associated with online learning in this context. According to the study, all three components have an effect on the online learning process. The three components include instructional materials, difficulties, and limits associated with online learning systems.